Origin, Epidemiology, Transmission, Clinical Symptoms, and Future Perspectives on Mpox Virus (MPXV): A Narrative Review (Journal of Current and Advance Medical Research, 2025)
Monkeypox (MPX) has long been a problem for many nations, particularly African nations, with recurring outbreaks in specific areas. The pathogenicity-dependent genetic variations, the mode of transmission, the lifestyle of the population, the growth in the number of viable hosts, alterations to their habitats, and the vaccination profile of humans are all directly related to the rate at which MPX spreads. Despite having a minimal potential for global transmission, it should be remembered that in today's globalized society, an unexpected breakout is always possible. One of the constant dangers to humanity is the advent of new diseases. New infections have the chance to develop as a result of ongoing environmental and human intervention. Human activity, international travel, and business frequently contribute to the spread of disease. The dynamics of mpox transmission and the progression of the disease are poorly understood. Controlling such outbreaks is mostly the responsibility of central organizations like the World Health Organization. However, maintaining good personal cleanliness, avoiding contact with used objects, and avoiding animal feces are the best ways to be safe. In 2022, the endemic disease status of MPX was revised to worldwide outbreak. This is the main cause for the condition's prevalence outside of Africa: it was deemed a worldwide health emergency, independent of travel restrictions. Clinical indications that are typical and serve as an indicator for the initial stage of diagnosis include fever, headache and muscle discomfort, enlarged lymph nodes, and skin rashes in certain body locations. The most popular and reliable diagnostic techniques are clinical symptoms and laboratory tests such as real-time PCR (RT-PCR) or traditional polymerase chain reaction (PCR). For symptomatic treatment, antiviral medications such as tecovirimat, cidofovir and brincidofovir are utilized. Although there isn't a vaccination specifically for MPXV, the smallpox vaccines that are now on the market increase the immunization rate. A greater understanding of MPXV transmission mechanisms by the general public could enable early identification of the spread of new cases to other populations.Journal of Current and Advance Medical Research, January 2024;11(1):41-49